Konflikt i cyberspace? Strategiske og juridiske implikationer - Anders Henriksen; Jens Ringsmose (Danish Institute for International Studies (DIIS), 2014)
– The proliferation of advanced information and communication technology has not only enhanced welfare and facilitated the exchange of ideas across national boundaries, but also led to an increasing vulnerability. As more and more of our economy, social, administrative and military activities are conducted through cyberspace, the risk of hostile and potentially harmful cyber activities increases. This report focuses on politically motivated hostile cyber-activities. Specifically, the report looks at three dimensions: A conceptual (what is a cyberattack and when - if ever - does it make sense to talk about cyberwar?), a strategic (how does the emergence and proliferation of "cyberweapons" affect political violence and modern armed conflicts in a strategic sense?), and a legal (how does political actors' use of cyberspace challenge the traditional legal concepts and categories, such as espionage, violation of sovereignty, force and armed attacks?). [...]
Keywords: 300